2020
DOI: 10.1371/journal.pone.0230880
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and associated factors towards diabetes mellitus among adult non-diabetic community members of Gondar city, Ethiopia 2019

Abstract: Introduction Diabetes mellitus is a metabolic disorder resulting from either loss of insulin producing cells, insufficient insulin action, or both. Knowledge can play an important role in preventing diabetes mellitus and its complications. There is limited information regarding knowledge and related factors regarding diabetes mellitus among non-diabetic adult community members in the study area. Therefore, the current study aimed to determine knowledge and associated factors towards diabetes mellitus among non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 21 publications
7
36
0
2
Order By: Relevance
“…This is supported by other studies (31,32). Participants who attended Bachelor degree were 6.5 times more likely to have good knowledge than lower educational level (diploma holders) which is supported by other study (31,33). The possible reason for this association might be because of increased in information as educational level increases.…”
Section: Discussionsupporting
confidence: 71%
“…This is supported by other studies (31,32). Participants who attended Bachelor degree were 6.5 times more likely to have good knowledge than lower educational level (diploma holders) which is supported by other study (31,33). The possible reason for this association might be because of increased in information as educational level increases.…”
Section: Discussionsupporting
confidence: 71%
“…Poor knowledge. Individuals who responded below the mean (19.37) of the total knowledge questions were considered to have poor knowledge about diabetes mellitus [26].…”
Section: Operational Definitionsmentioning
confidence: 99%
“…These results are consistent with other studies [ 64 , 65 ]. Educational level was significantly associated with better attitudes and practices that helps in controlling diabetes [ 64 , 65 , 66 , 67 , 68 ]. A recent study revealed that people with educational qualifications had good knowledge regarding diabetes compared to those who could not read and write [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Educational level was significantly associated with better attitudes and practices that helps in controlling diabetes [ 64 , 65 , 66 , 67 , 68 ]. A recent study revealed that people with educational qualifications had good knowledge regarding diabetes compared to those who could not read and write [ 66 ]. The HbA1c levels were highest among low-educated adults, and death risks associated with uncontrolled HbA1c were significantly greater [ 67 ].…”
Section: Discussionmentioning
confidence: 99%